Evaluation of the weighted level of damping of bounded disturbances in descriptor systems - Mazko, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We establish necessary and sufficient conditions for the validity of the upper bounds for the performance criteria of lineardescriptor systems characterizing the weighted damping level of external and initial disturbances. The verification of theseconditions is reduced to solving matrix equations and inequalities. The main statements are formulated with an aim of theirsubsequent application in the problems of robust stabilization and in the $H_{∞}$ -optimization problems for descriptor controlsystems.